Financial Innovation and Crowdfunding: Influencing Investment Decisions in Tech Startups - Kaimuk Panitkulpong; Amnuay Saengnoree; Thapong Teerawatananond (My University, 2024)
This study investigates the financial behavior of Thai investors in equity crowdfunding (ECF), focusing on the factors that influence their investment intentions. Drawing upon the Information System Success Model (ISSM), the Theory of Diffusion of Innovations, and the Technology Acceptance Model 3 (TAM3), the research examines the platform quality (PQ), platform characteristics (PC), and social influence (SI) as independent variables, with the perceived usefulness (PU) and perceived ease of use (PEOU) acting as mediators. Data were gathered from 275 Thai investors and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that the PU significantly influences investment decisions both directly and indirectly through the PEOU, which also directly affects investment intention. Furthermore, SI, PC, and PQ have indirect effects on investment decisions via the PU and PEOU, with SI being the most influential factor. This study provides valuable insights into optimizing ECF platform design, fostering investor trust, and enhancing regulatory frameworks to facilitate financial inclusion and innovation in the Thai crowdfunding landscape.
Keywords: Investment; High tech; Financial Innovation; FinTech, Crowdfunding, Digital Finance